PENGARUH KONSENTRASI ETANOL SEBAGAI PELARUT PENGEKSTRAKSI TERHADAP KADAR NAFTOKINON DALAM EKSTRAK DAUN PACAR KUKU (Lawsonia inermis L.) - Zainab Zainab (Universitas Ahmad Dahlan, 2013)
The extract quality can be affected by the components and concentration of chemical compounds contained in the extract.Type and quantities of chemical compounds that are dissolved in the extraction process is strongly influenced by the solvent extraction. The aim of this study is to determine the effect of concentration of ethanol as solvent extraction on naphthoquinone content in Henna leaves extract. The extraction method was done by maceration for one hours with water, ethanol 50% , 70% , 90% and 95% v/v solvens of the dried Henna leaves powder. Each macerate was made 5 % w/v concentration and than was spotted 5 µL on plate of silica gel F 254 and eluted with mixture of chloroform - methanol (17:3 v/v) as mobile phase. The spots on chromathogram were scanning and measured the area under curve with TLC densitometer at maximum wave lenght. The results showed that spot at Rf 0.31 had similar spectra with naphthoquinone standard and same maximum wavelength at 279 nm. The result of solvent optimization indicated that the best solvent extraction for Henna leaves was ethanol 50% v/v with the highest naphthoquinone contentat 1.43 ± 0.1942% w/v.